Dynamic monitoring of NET activity in mature murine sympathetic terminals using a fluorescent substrate. - Parker, L; Shanks, J; Kennard, J; Brain, K (2010)
BACKGROUND AND PURPOSE: To validate a fluorescence approach for monitoring norepinephrine transporter (NET) transport rate in mature sympathetic terminals, and to determine how prejunctional muscarinic receptors affect NET rate. EXPERIMENTAL APPROACH: Confocal imaging of a fluorescent NET substrate [neurotransmitter transporter uptake assay (NTUA)] as it accumulates in the mature sympathetic nerve terminals of the mouse isolated vas deferens. Fluorescence recovery after photobleaching (FRAP), enhanced green fluorescence protein (EGFP)-transgenic mice and contraction studies were also used. KEY RESULTS: NTUA fluorescence accumulated linearly in nerve terminals, an effect that was prevented with NET inhibition with desipramine (1 microM). Such accumulation was reversed by amphetamine (10 microM), which is known to reverse the direction of transport of NET substrates. NTUA labelling was not present in cholinergic terminals (identified using EGFP fluorescence expressed in transgenic mice under a choline acetyltransferase promoter). FRAP experiments, altered nerve terminal distribution with reserpine pretreatment and co-imaging in terminals filled with a cytoplasmic marker (Alexa 594 dextran) indicated that the NTUA labelling was largely confined to vesicles within varicosities; vesicular exchange between varicosities was rare. The rate of NTUA accumulation was slower in the presence of the muscarinic agonist carbachol (10 microM) demonstrating muscarinic inhibition of NET rate. CONCLUSIONS AND IMPLICATIONS: A straightforward protocol now exists to monitor NET transport rate at the level of the single nerve terminal varicosity, providing a useful tool to understand the physiology of NET regulation, the action of NET inhibitors on mature sympathetic terminals, dynamic vesicular tracking and to identify sympathetic terminals from mixed terminal populations in living organs.